A study to investigate the impact of social research toward research productivity - Kaba, Abdoulaye; A. El Refae, Ghaleb; Eletter , Shorouq; Yasmin , Tahira (Journal of Eastern European and Central Asian Research (JEECAR), 2021)
The main purpose of this study is to investigate the relationship between demographic diversity and research productivity. The paper attempts to identify the influence of gender diversity, college diversity, and diversity in collaboration on the research productivity of faculty members. The paper is based on data collected from the Deanship of Scientific Research and the Office of Documentation, Al Ain University (AAU). The findings of the study showed significant differences in college diversity. Faculty members of the English instruction colleges dominated the leadership in research productivity. The independent variables appeared to predict 23% of the variation in research productivity. AAU faculty members should increase internal and external collaborations and network in scientific research. Similarly, AAU also should support and promote research collaboration and networking among faculty members through a comprehensive strategic plan and guidance for internal and external collaborations.